Universal efavirenz determination in transport study, rat placenta perfusion and placenta lysate by HPLC-UV - Zelena, Lucie; Reznicek, Josef; Ceckova, Martina; Sklenarova, Hana (Journal of pharmaceutical and biomedical analysis, 2017)
Efavirenz is an antiretroviral drug used in the treatment of HIV-positive patients. A simple, fast and sensitive high-performance liquid chromatography (HPLC) method was developed in order to determine efavirenz in three types of samples provided from pharmacokinetic studies. The analysis took 5min and was performed using a C18 analytical column (Discovery HS C18, 150×4.6mm, particle size of 5μm) in isocratic mode with a mobile phase containing acetonitrile and water (65:35, v/v), a flow rate of 1.6mLmin-1, a sample volume of 10μL and UV detection at 245nm. Three different sample matrices (Opti-MEM medium, Krebs perfusion liquid and tissue lysate) and their treatment (dilution, SPE) were considered. The validated method was applied for the analysis of 805 real samples arising from in vitro transcellular transport assays and in vivo organ perfusion experiments in order to evaluate the interaction of efavirenz with ATP-dependent drug efflux transporters. The lack of interaction of efavirenz with ABCB1, ABCG2 and ABCC2 transporters as well as technical aspects of this analysis, including the adhesion of efavirenz to the plastic materials and the stability of the drug during different tissue lysis approaches are discussed.
Keywords: Cyclopropanes; Chromatography, High Pressure Liquid; psi; Alkynes; Drug Stability; Pregnancy; ATP Binding Cassette Transporter, Subfamily G, Member 2; ATP Binding Cassette Transporter, Subfamily B, Member 1; Dogs; Multidrug Resistance-Associated Proteins; protein spojený s mnohočetnou rezistencí k lékům 2; Multidrug Resistance-Associated Protein 2; Placenta; Female; alkyny; krysa rodu Rattus; Stability; zvířata; cyklopropany; potkani Wistar; reprodukovatelnost výsledků; Perfusion; buňky MDCK; buněčné linie; biologický transport; P-glykoprotein; ženské pohlaví; Cell Line; Rats, Wistar; Reproducibility of Results; proteiny spojené s mnohočetnou rezistencí k lékům; Madin Darby Canine Kidney Cells; Drug transporters; perfuze; Drug-drug interactions; benzoxaziny; těhotenství; Liquid chromatography; acetonitrily; Rats; stabilita léku; Animals; Efavirenz; Pharmacokinetics; placenta; ABC transportér z rodiny G, člen 2; Acetonitriles; vysokoúčinná kapalinová chromatografie; Benzoxazines; Biological Transport